If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/3(x-4)=3/4(x+2)
We move all terms to the left:
5/3(x-4)-(3/4(x+2))=0
Domain of the equation: 3(x-4)!=0
x∈R
Domain of the equation: 4(x+2))!=0We calculate fractions
x∈R
(20xx/(3(x-4)*4(x+2)))+(-9xx/(3(x-4)*4(x+2)))=0
We calculate terms in parentheses: +(20xx/(3(x-4)*4(x+2))), so:
20xx/(3(x-4)*4(x+2))
We multiply all the terms by the denominator
20xx
Back to the equation:
+(20xx)
We calculate terms in parentheses: +(-9xx/(3(x-4)*4(x+2))), so:We get rid of parentheses
-9xx/(3(x-4)*4(x+2))
We multiply all the terms by the denominator
-9xx
Back to the equation:
+(-9xx)
20xx-9xx=0
| -12x^2-24x+6x=0 | | 3x-5=5x+25. | | (t+1)^2*(t-8)^2=45 | | 3x+3=-ģx+12 | | -3(x+5)=16 | | -3(5n-4)=33 | | -5-4=6f+26 | | 11p=-12+5p^2 | | 3x+21=x-19 | | 3(x-2)-12x=29-4x | | -4r-7=29 | | ((t+1)^2)*((t-8)^2)=45 | | 5a-a-3a+1=19 | | 3(w+7)+2w=-4 | | j-994=248 | | 7y+5+3y+5=-22 | | 30+12w=198 | | 109=g-21 | | 11+x2=11x | | -11h+18h-8h=-15 | | -32=(-2z+3+5) | | 6x-2-3x=-5x+10 | | -14=-2u+4(u-4) | | 12-2v=10 | | 16x+7-7x-15=10 | | 11+x²=11x+x² | | 5+3x=x-20 | | ((t+1)^2)((t-8)^2)=45 | | 3(c-4)=13 | | 2b-1=4b-26 | | v-298=396 | | 2Y=12-3y |